The Antioxidant Test And Determination OfPhenolic Content In Packaged Green Tea Using The FRAP Method - Nugraha, Novanda Satria; Listyani, Tiara Ajeng; Septiarini, Anita Dwi (Science and Community Pharmacy Journal, 2022)
The tea plant is one of the plants belonging to the Camellia genus which is widely spread in Southeast Asia. There is an assumption in the community that packaged green tea is good for consumption since green teadoes not undergo fermentation, consequently it has a higher antioxidant activity. Polyphenols present in tea provide an antioxidant activity that can be used to prevent cardiovascular disease, cancer, inflammation, and diabetes. This study aims to examine the antioxidants and determine thephenolic content of packaged green tea using the FRAP method. This research was carried out using a simplified assay for phenolic content determination and using a UVVisible spectrophotometer with folic ciocalteu reagent and using gallic acid as a comparison. Antioxidant activity was tested using the FRAP method with vitamin C as a comparison, which was measured using a UV-Visible Spectrophotometer. The total phenolic content contained in green tea extract A packaged was 0.2604 mg GAE/g green tea B packaged was 0.2656 mg GAE/g green tea extract C packaged was 0.2556 mg GAE/g. Packaged green teaextract A, packaged green tea B, and packaged green tea C had antioxidant capacities equivalent to ascorbic acid, namely green tea extract A 77.761 mg AAE/g, green tea extract B packaged 76.809 mg AAE/g and green tea extract C packaged which is equivalent to ascorbic acid, namely 74.904 mg AAE/g extract. The highest antioxidant value was green tea extract A packaged at 77.761 mg of Ascorbic Acid Equivalent/ gram of extract.